Tranformation of scholarly publishing in the digital era: scholars' point of view - Vrana, Radovan (Array, 2011)
Scholarly publishing is one of the most important activities for scholars whose career depends on publication of their research results. To find out more about the current situation regarding scholarly publishing at the Faculty of Humanities and Social Sciences in Zagreb, Croatia, a research project was initiated. Findings showed strong orientation of scholars towards the most traditional publication channel in science - printed journal. Findings also revealed that scholars most frequently write their articles alone ; sometimes they wait for more than a year for publication of their articles mainly in journals ; they are seldom editors of journals, but they participate in work of editorial boards and they also participate in the peer review. The outcomes of this research showed that scholars are still communicating by using the infrastructure of the old paradigm of scientific communication based on printed information resources and that they suffer from the same problems as their colleagues around the world regarding communication of the results of their scientific research.